Filtering of dried fish to separate waste - Mumbai Archive Project Team (Jio Institute, 2024)
Dried fish is filtered to separate waste, which is collected and sold. Fish waste is composted into khad (organic fertilizer) for use in agriculture and horticulture. Fish-based fertilizers are rich in nutrients such as nitrogen, phosphorus, and potassium, which promote plant growth and improve soil fertility.